Functional Analysis of Potato CPD Gene: A Rate‐Limiting Enzyme in Brassinosteroid Biosynthesis under Polyethylene Glycol‐Induced Osmotic Stress. Issue 5 (1st September 2016) - Zhou, Xiangyan; Zhang, Ning; Yang, Jiangwei; Si, Huaijun
Abstract : The constitutive photomorphogenesis and dwarf ( CPD ) gene was initially isolated from an Arabidopsis thaliana (L.) Heynh. cpd mutant and encodes C‐3 oxidase as a key rate‐limiting enzyme in the brassinosteroids (BRs) biosynthesis pathway. For a better understanding of the molecular mechanism of CPD gene overexpression in potato ( Solanum tuberosum L.) and CPD ‐overexpressing potato plant tolerance to polyethylene glycol (PEG)‐induced osmotic stress, CPD gene was cloned by reverse transcription–polymerase chain reaction (RT‐PCR) from potato. The coding region was 1473 bp and encoded a deduced protein of 490 amino acids. The transgenic potato plants with CPD gene overexpression were obtained. Quantitative real‐time polymerase chain reaction (qRT‐PCR) analysis indicated that the CPD gene expressed in the roots, stems, and leaves of the transgenic and nontransgenic (NT) plants with particularly enhanced expression in the leaves. The proline content was 0.18‐ to 0.62‐fold higher and the malonaldedyde (MDA) content decreased by 45.1 to 87.4% in CPD ‐overexpressing potato plants than in the NT plants under PEG‐induced osmotic stress conditions. The soluble sugar content, soluble protein content, and the superoxide dismutase (SOD), peroxidase (POD), catalase (CAT), glutathione reductase (GR), and ascorbate peroxidase (APX) activities were all greater in the drought‐stressed transgenic plantlets at different sampling times than in the NT seedlings. These results indicated that CPD gene overexpression could ameliorate the effects of PEG‐induced osmotic stress. These results lay the foundation for further research on BR regulation in potato development and growth.